Recent advances in craniopharyngioma pathophysiology and emerging therapeutic approaches - Pires de Oliveira Neto, Clariano; Nascimento, Gilvan Cortês; Damianse, Sabrina da Silva Pereira; Faria, Manuel dos Santos (Frontiers in Endocrinology, 2025)
Craniopharyngiomas are rare intracranial tumors originating from the Rathke’s pouch, affecting the sellar and parasellar regions. Despite their benign nature, they cause significant morbidity and mortality due to their proximity to vital structures such as the optic pathways and the hypothalamic-pituitary axis, resulting in endocrine, visual, neurological impairment, and hypothalamic syndrome. Classified into adamantinomatous (ACP) and papillary (PCP), these tumors differ in epidemiology, histology, and pathophysiology. ACP, the most common type, presents a bimodal peak incidence between 5 and 15 years of age and 45 and 60 years of age, while PCP is more restricted to adults. Traditional treatments such as surgery and radiotherapy face significant challenges, including high recurrence rates. Intracystic chemotherapy is used in monocystic ACP but with limited efficacy and adverse effects related to toxicity. Recent advances in molecular biology have introduced targeted therapies, such as BRAF and MEK inhibitors, which show potential benefits in craniopharyngioma patients, particularly in the PCP. For ACP, however, therapeutic outcomes remain limited despite advances in molecular understanding, including mutations in the CTNNB1 gene and growth factors. Increasing investigation into the inflammatory microenvironment and immune response of these tumors presents new therapeutic possibilities and promising alternatives for tumor control, such as the use of anti-IL-6R, anti-VEGF agents and immune checkpoints inhibitors. This review aims to synthesize advancements in the pathophysiology of craniopharyngiomas and explore emerging therapeutic implications, focusing on precision medicine approaches for the management of this challenging disease.